POLA JARINGAN KOMUNIKASI STRUKTUR FANS CLUB LIVERPOOL JAKARTA - Muhamad Faddli Ramadhan (2023)
This study aims to determine the centrality within the Liverpool Jakarta fan community by using organization communication theory, and also to determine the roles of other members in the communication network formed within Big Reds Jakarta (Liverpool Jakarta fan community). The method used is a quantitative method of communication networks by taking datapremier namely a questionnaire taken from 23 members of the Big Reds Jakarta community in which there are questions about actors, relations between actors and other actors who become sociographics and the value of communication networks using the UCINET application. The result of this research is that the researcher finds the dominant actors in level centrality, intermediary centrality, closeness centrality and eigenvector centrality. Researchers also found a roleold worries andopinion leader, from the graph of the communication network that is seen, you can see whereopinion leader shown. Looking foropinion leader seen by all network members can be seen from researchers participating in activities carried out by the Jakarta Big Reds community. Roleopinion leader as an intermediary and information controller for activities carried out by Big Reds Jakarta. Big Reds Jakarta makes social activities asculture they are in connecting all relationsfans Liverpool FC who can create a high sense of togetherness and have a sense of belonging to the community, so that the existence of the community will always exist for the long term. From the analysis of communication networks carried out at the actor level it is very important to look for actors who have the highest centrality value in sharing information from the value of the actor who has the highest centrality value seeing that the actor is very dominant in the community communication network.